Negative impact on clinical outcome of the mutational co-occurrence of SF3B1 and DNMT3A in refractory anemia with ring sideroblasts (RARS). Issue 7 (3rd July 2017) - Martín, Iván; Such, Esperanza; Navarro, Blanca; Vicente, Ana; López-Pavía, María; Ibáñez, Mariam; Tormo, Mar; Villamón, Eva; Gómez-Seguí, Inés; Luna, Irene; Oltra, Silvestre; Pedrola, Laia; et al.
Abstract: The incidence of SF3B1 mutations in patients with RARS is high. Recently, it has been shown that SF3B1 and DNMT3A mutations overlap more often than expected, although it is not clear how this could affect the disease. We studied SF3B1 and DNMT3A in 123 RARS patients: 101 out of 123 samples (82%) had somatic mutations in SF3B1, and 13 of them (13%) showed a co-mutation ( SF3B1 mut DNMT3A mut ). All co-mutated patients had a normal karyotype, and 12 of them (92%) were lower-risk patients (IPSS and IPSS-R). Despite their favorable profile, SF3B1 mut DNMT3A mut patients showed a higher RBC transfusion dependency (92% versus 48%, p = .007), a shorter overall survival (OS) (median, 30 versus 97 months, p = .034), and a higher risk of progression to acute myeloid leukemia (AML) at 5 years (25% versus 2%, p = .023) than SF3B1 mut DNMT3A wt patients. In conclusion, DNMT3A mutations are present in a significant proportion of SF3B1 mut patients with a negative clinical impact.